AN EFFORT TO PRESERVE NATIONAL CULTURE BY CREATING BATIK MOTIFS ON WOMEN'S CASUAL CLOTHING WITH THE THEME OF LARUNG SESAJI - Elisa Bella Anggita; Guntur (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2024)
The work entitled An Effort to Preserve National Culture by Creating Batik Motifs on Women’s Casual Clothing with the Theme of Larung Sesaji was created to satisfy the interest of revealing the meaning behind the celebration of Larung Sesaji. The work is aiming at creating a new batik motif with theme of Larung Sesaji as well as an identification of Indonesian culture applied in women’s casual wear. The creator hopes that this effort can inspire the other creators to contribute to promote Indonesian culture through their works. This creation uses three stages and six steps, namely data collection stages, design stages, and embodiment stages. Data collection stage was conducted through an observation at the ceremony of larung sesaji. The collected data are then be used as a substance for the design stages, namely to design or visualize the source obtained into an alternative, selected, and perfected designs. The embodiment stage or making real works of batik was conducted with the cover dye technique employing natural colors and then sewing it to create casual clothing for women. The work managed to create four fashion creations, entitled Bahtera Sagara by the name of Lakara Meraki motif, Rahsa Linuhung in the name of Abyudaya Dakara motif, Grahita Sampena by the name of Hirap Mara motif, and Dahayu Kalis by the name of Asa Arshaka motif. Each creation is complemented by accessories such as earrings, hair ornaments and shoes. By this work, the creators try to introduce the public, especially young people, the idea of the important of preserving Indonesian culture.